أثر قاعدة "إعمال الكلام أولى من إهماله" في تفسير النصوص الشرعية دراسة نظرية تطبيقية - بده زكري, كلثوم (University of Eloued-جامعة الوادي, 2015)
Multi rules large door in jurisprudence; the mind of the evidence sentences, which extrapolates including governance, or through detailed evidence from the Quran and Sunnah, and individual topics of this kind of rules varies depending on their relationship to terms that religious texts, and al-Qaida subject of the study; base, "the realization of the speech first of neglect "; officer base of the meanings of the legitimate text, taking phenomena texts, realities, and suspend interest for the development of legitimate governance, not distracted by the metaphors texts, but considerable, not to neglect to speak, taking Bmanih possible presumption, so that the provisions relating to these meanings are not canceled, when it is not apparent; The realization of speech and duty in forensic text; which is not what makes no sense, no sense of nonapparent, to understand the legal text on the possible meanings, and also to the Islamic ruling based on the consideration of these meanings, and believe right there
مذكرة ماستر
Keywords: النصوص الشرعية/إعمال الكلام/إهمال الكلام; Sharia texts / realization of speech / neglect of speech